Narrativas entrecruzadas de professoras negras em terras de Gaudérios - GOULART, Treyce Ellen Silva (Universidade Federal do Pará, 2021)
This paper presents the investigative paths covered by autobiographical narratives of three black female teachers in city Rio Grande/RS city. The production data was inspired by the methodology of biographical workshops and were obtained through collective and individual meetings at school in which the teachers worked, between 2014 and 2015. were problematized from a theoretical and political perspectives of Cultural, Feminist and Decolonial Studies and an intersectional bias. The approaches with the subjects’ narrations provided an understanding of the various crossings and overlaps between the issues of race/racism, gender/sexism and class/classism in order to realize these elements not as solid, atomic or immutable structures, but as an amalgam it is interpreted/challenged and interprets/challenges the subjects in their daily lives.